Implementation of Digital Transformations in the Economy of the Republic of Kazakhstan - A, Petr Hajek; A., Tovma N.; T. Аkimbaeva K.; S., Kyzdarbekova A.; K., Kupenova J. (Farabi Journal of Social Sciences, 2019)
The introduction of technologies of digitalization of the economy, allowing the state, business and society to interact effectively, is becoming an increasingly large-scale and dynamic process. The purpose of the study is to analyze the current state of implementation of digital transformation in the economy of the Republic of Kazakhstan. During the years of independence, we have managed to become one of the 50 most competitive countries in the world. Digitalization is necessary to improve the competitiveness of enterprises and the country as a whole, as well as to improve the quality of life of the population. The digitalization program is a great journey, not a project with some ending, it will live for many years and constantly improve. At present, global economic growth will depend on the quality of market institutions, productivity and capital growth through continued investment and the use of intellectual capacity, combined with modern information and digital technologies, and healthy and growing competition. The results of the study ‒ analyzed the totality of all factors affecting the development of the digital economy, identified the main trends and shows the current state of the digital economy of the Republic of Kazakhstan. To promote the growth of the digital economy, measures of economic policy should be aimed at encouraging investment in productive capital and the stimulation of innovation through increased support of research and development, the introduction of tax incentives and subsidies, increasing productivity growth by improving the quality of education. The research methodology is focused on the use of a complex research method, methods of statistical, comparative, logical-structural and factor analysis are also used. Now there is a task to enter the number 30, which requires new innovative development and accelerated technological renewal from Kazakhstan. Scientific results will contribute to the development of the digital economy, focused on improving efficiency and competitiveness. This will improve the business and innovation climate in the Republic of Kazakhstan.